Exploring ash fusion characteristics and thermal decomposition of biomass through thermogravimetric analysis - Sachin Channappa Hallad; N. L. Panwar; V. Kavan kumar (Sustainable Energy Research)
Abstract This study aims to investigate the ash fusion properties along with thermogravimetric examination of different biomass in an inert atmosphere at 20, and 30 °C/min. According to the accepted procedures, the physicochemical characterizations of biomass Sawdust, Soybean (Glycine max) as well as Eucalyptus (Eucalyptus globulus) were completed. Thermodynamic and kinetic parameters were determined within the active pyrolysis zone using iso-conversional models like FWO and KAS techniques. During thermal deterioration, biomass loses mass through moisture loss, passive and active pyrolysis. The active pyrolysis zone was responsible for 50–55% of the mass loss between 180 and 395 °C. The activation energy values were 175.08and 174.21 kJ/mol based on KAS and FWO models, respectively, for sawdust; 153.15 and 151.47 kJ/mol for soybean and for eucalyptus 168.70 and 167.70 kJ/mol, respectively. The ash fusion behaviours of biomass showing 1506 °C deformation temperature for soybean followed by 1465 °C for eucalyptus and 1289 °C for sawdust and their variation processes under decreasing atmosphere were examined to reduce ash-related problems during gasification.